Some Proximate Components of Sweet Potato Tubers (SPTM), Plant Fractions and by-Products and the Effects of Inclusion of Varying Levels of SPTM on Pig Performance and Carcass Characteristics (Journal of Science and Technology, 2016)
Studies were conducted to determine some proximate components of products and by-products of the sweet potato variety, Sauti, and to determine the growth performance and carcass characteristics of pigs fed diets containing varying levels of sweet potato tuber meal (SPTM). The sweet potato vines (SPV) contained 10.5%CP, 38.7%CF, 1.9%EE and 6.6%Ash. The corresponding values for the leaves (SPL), tuber residues (SPTR), peels (SPP) and feed-grade tuber (SPTM) were 12.0, 3.2, 7.1, and 7.6%CP; 18.4, 5.2, 6.7 and 2.9%CF; 3.0, 1.5, 3.9 and 2.0%EE and 12.2, 0.5, 5.8 and 4.3% Ash. Isonitrogenous (18%CP), diets containing 0.10, 20 and 30% SPTM which replaced similar levels of maize were formulated and fed to a total of 16 starter-grower pigs which had been housed in individual welded-mesh cages and provided with feed and water ad libitum. The feeding trials lasted 8 weeks after which all the pigs were slaughtered for carcass evaluation. The values for the mean daily feed intake, weight gain and feed conversion efficiency (FCE) were similar (p>0.05) for the pigs and on the 4 dietary treatments. Feed cost was lowered as the level of SPTM in the diet increased from 0 to 30%. However, the feed cost/kg liveweight gain tended to be higher in the SPTM containing diets. This was attributed to the poorer FCE values of such diets. With the exception of the relative viscera and liver weights which were significantly (p>0.05) higher for the pigs fed the SPTM diets, all other carcass trait values were similar (p>0.05). it was concluded that sweet potato products and by-products could assist in meeting the nutrient needs of pigs in Ghana. However, it may be necessary to ensure that their use reduces not only feed cost but also feed cost/kg liveweight gain – a very important economic parameter.